Symptomatology of Allergic Diseases in Surxondaryo Region - Aliniyozovich, Xolboyev Norbek (American Journal of Bioscience and Clinical Integrity, 2025)
The prevalence of allergic diseases in the Surxondaryo region is a pressing issue, еt research considering the region’s unique ecological and climatic conditions remains insufficient. This article provides data on the factors contributing to the spread of allergic diseases, their clinical symptoms, and risk groups. Data were collected through epidemiological surveys and clinical observations, followed by statistical analysis. The findings revealed that diseases such as allergic rhinitis and asthma are highly prevalent due to the dry climate and local allergens. The article offers recommendations to strengthen preventive measures and implement specialized diagnostic methods.